PENENTUAN POLA OPERASI PINTU PELIMPAH DALAM RANGKA PENGENDALIAN BANJIR BENDUNGAN DELINGAN, JAWA TENGAH - Ariberto Jonathan; Doddi Yudianto; S Sanjaya (JURNAL TEKNIK HIDRAULIK, 2021)
A spillway is one of many important components of a dam, which is operated to prevent the dam from overtopping. Spillway with gate structures requires to have a good operation pattern by considering a minimum critical height and outflow discharge to prevent any flooding events in the downstream part of the spillway channel. The case study in this research is the Delingan Dam which has two ogee spillways, four main sluice gates and four additional sluice gates. Located in Karanganyar District, West Java, Delingan Dam is considered as a vast infrastructure which is potentially threatening if the spillway’s operation is not optimal. This study aims to analyze the spillway gate operations’ pattern of Delingan Dam in order to control the flooding event. The methodology used in this study is flood routing by utilizing several scenarios in order to obtain the optimal simulation results. Five scenarios that were simulated on the designated flood discharge have various combinations on the number of gates and their opening, as well as the time in which the operation started. The results show that the operation only using ogee spillway still meets the criteria for minimum critical height and maximum allowable discharge for return period of 25, 50, and 100 year.As the discharge with 1000 year return period, half of PMF, and PMF,the recommended operation is, foremost, to occupy the main gate in which results in the peak outflow discharge of 23.65 m3/s, 62.4 m3/s, and 140.9 m3/s, with the minimum critical height of 1.45 m, 1.41 m, and 1.35 m, respectively. However, this operation is not adequate for the half of PMF, and the PMF discharge, since the capacity in the spillway channel is estimated about 24.7 m3/s.Keywords: spillway, flood control, spillway gate operation, the delingan dam